The Effectiveness Of Nutrition Education on Improving the Nutritional Status of Pregnant Women at the South Bulango Public Health Center - Nur Fadhilah R. Husain; Raden Maria Veronika Widiatrilupi (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Background: Maternal nutritional status plays a crucial role in determining both maternal and neonatal health outcomes. According to data from the Indonesian Ministry of Health (2021), the prevalence of anemia among pregnant women reached 48.9%, while in Gorontalo Province, around 30% experienced malnutrition. Poor nutritional status during pregnancy is associated with increased risks of complications, including preterm birth, low birth weight, and higher maternal and neonatal mortality rates. Therefore, nutrition education is considered an essential strategy to enhance knowledge and promote adequate dietary intake among pregnant women.Objective: This study aimed to evaluate the effectiveness of nutrition education in improving the knowledge and nutritional status of pregnant women at the South Bulango Community Health Center. Methods: A quantitative study with a pre-experimental design was conducted involving 30 pregnant women selected through purposive sampling. Inclusion criteria included women aged 18–35 years, free from severe comorbidities, and willing to participate. Data were collected using questionnaires to assess nutritional knowledge, interviews to explore dietary patterns, and anthropometric measurements such as weight, height, and mid-upper arm circumference (MUAC). Data analysis employed descriptive statistics and the Wilcoxon test to assess differences before and after the intervention. Results: Most participants were aged 20–35 years (66.6%), had secondary education (63.3%), and were housewives (60%). Post-intervention results showed a substantial increase in good nutritional knowledge from 13.3% to 60%. Nutritional status also improved progressively across trimesters, with normal MUAC increasing from 33.3% to 60%, while undernutrition declined from 50% to 13.3%. The Wilcoxon test indicated a significant difference (p = 0.000; p < 0.05). Conclusion: Nutrition education effectively enhances both knowledge and nutritional status among pregnant women and should be integrated into routine antenatal care services.